Higher Education Research Collaboration to Support Excellence and Competitiveness - Cudai Nur, Andi; Sofia Rukmana, Novayanti; Nuryamin, Muhammad; Ali Qalati, Sikandar; Ali, Wazir (Iapa Proceedings Conference, 2023)
This manuscript is the result of research which aims to understand the reality of LP2M UNM collaboration which is implemented in research by collaborating with universities, schools, communities, private and government institutions. The methodology used is qualitative with interview techniques, documentation and observation. Qualitative analysis approach with steps of data collection, reduction, data presentation, and drawing conclusions. The data sources are documents, observations and interviews with informants who are directly related to the implementation of the collaboration, as well as several internal and external stakeholders involved. The argument from the results of this research is that "collaborative research in higher education can be of high quality if it is built from a study program based on the root of the problem, and has support from various interested parties, and is carried out in an integrated manner. in accordance with what has been agreed." There is also a cooperation agreement so that intensive relationships are established between all parties, and the implementation of the collaboration has opened a partnership network to share resources with various parties. The research conclusions are as follows: (1) The implementation of the collaboration has achieved its objectives; (2) Utilization of resources (people, facilities and funds) in implementing collaboration has been fulfilled; (3) Collaboration has supported the quality of research processes and products, as well as making a positive contribution to LP2M UNM, although not yet optimal. There are still support and obstacles from an economic, social and political perspective.